SERVANT LEADERSHIP LEARNING STRATEGY IMPLEMENTATION FOR SPIRITUAL FORMATION OF HIGH SCHOOL STUDENTS AT THE ATHALIA SCHOOL - Sanga, Victor Sumua; Khoe Yao Tung (Sekolah Tinggi Teologi Moriah, 2024)
Strong leadership is crucial for success in the 21st century. However, student leadership development has yet to be consistently implemented for all students. Servant leadership is considered the best model for high school students, but research on this model is limited in that context. Previous studies focused on servant leadership's contribution to spirituality but were confined to theological education. Further research is needed to provide servant leadership training in a broader student context. Athalia High School aims to develop servant leaders and requires sufficient data on the impact of servant leadership strategies on students' spiritual formation to realize the school's vision. This qualitative phenomenological study addresses these challenges. Eight students participating in the spiritual formation project within the servant leadership program at Athalia High School were interviewed using purposive sampling. The study reveals that servant leadership learning facilitates students' spiritual formation, with four common themes emerging: self-awareness, meaningful routines, life changes, and challenges in spiritual formation. These findings emphasize the importance of implementing servant leadership principles to foster students' spiritual growth and leadership abilities. Kepemimpinan kuat merupakan kebutuhan untuk berhasil di abad ke-21. Sayangnya, pengembangan kepemimpinan murid belum dilakukan reguler, untuk semua murid tanpa kecuali. Meski ahli meneguhkan bahwa model kepemimpinan terbaik untuk dikembangkan bagi para murid di sekolah menengah adalah servant leadership, namun penelitian model kepemimpinan ini juga masih sangat kurang di jenjang tersebut. Penelitian servant leadership yang berkontribusi bagi spiritualitas memang pernah dilakukan sebelumnya karena kesadaran akan saling pengaruh positif antara kepemimpinan dan spiritualitas, namun implementasinya masih terbatas pada pendidikan teologi. Penelitian selanjutnya membutuhkan pelatihan servant leadership untuk pendidikan menengah dalam konteks murid yang lebih luas. SMA Athalia membentuk muridnya secara reguler untuk mampu memimpin dengan cara dan prinsip servant leader. Namun SMA Athalia membutuhkan data yang cukup sejauh mana implementasi strategi pembelajaran servant leadership yang diterapkan dapat membangun formasi spiritual murid sehingga dapat mewujudkan visi sekolah. Penelitian kualitatif fenomenologi ini dirancang untuk berkontribusi bagi kendala-kendala di atas. Sumber data penelitian ditentukan dengan purposive sampling yang dihimpun melalui wawancara kepada delapan murid SMA Athalia yang memilih formasi spiritual dalam proyek penerapan karakter servant leadership. Hasil penelitian menunjukkan pembelajaran servant leadership memfasilitasi murid mengalami formasi spiritual. Ada empat tema umum yang dialami: kesadaran diri, rutinitas bermakna, perubahan hidup, dan tantangan formasi spiritual.